Mengoptimalkan Kinerja SDM Dalam Peningkatan Inovasi Bisnis - Amirah Yudhaputri, Egabetha; Hartini Rahayu, Dwi; Aryani Tribudhi, Debbie; Ciro Delvecchio, Buffon; Azzahra, Sabrina (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2023)
The era of digitalization requires development in digital skills. These skills are not only needed for students but also for business people who want to develop businesses, especially creative businesses. It requires solid teamwork, creative ideas and the right HR strategy, especially HR planning that can adapt to the digital world. Community Service - PKM currently being held by FEB Usakti, aims to form a team within the organization that is open to creative and innovative ideas in business, as well as improving human resources within the organization. The method for implementing this PKM is carried out by means of counseling to improve HR performance with a knowledge delivery approach by means of socialization, introduction to the scope of independent business activities that can be carried out, then educational training to improve HR by exploring each potential and managing each ability for appropriate activities (job analysis), as well as training to form creative and digital business and marketing teams. The results are expected for participants to be able to optimize their efforts.